Significados e experiências de pessoas em situação de rua acometidas por tuberculose - Barbosa, Khivia Kiss da Silva (2018)
Introduction: The presence of people living on the street (PSR in Portuguese) awakens in our society indifferent looks which marginalize and associate this public with violence. Sick of tuberculosis (TB) while living on the street greatly potentiates this segregation. Given that TB is a disease that is strongly marked by social exclusion and stigma. Dwelling in the street and being affected by this disease, there is a requirement for a (re)organization in ways of living and meaning of life due to the repercussions that the illness produce in the existence of the sick people and their social environment. Objective: To analyze the meanings and experiences of street dwellers in relation to tuberculosis in the street. Methodological approach: A qualitative study, developed in the city of João Pessoa, which involves five RSPs, affected by TB. To collect the data we used a field diary and a roadmap of in-depth interviews from February 2015 to March 2016. To break down the empirical material, a narrative analysis was used. After dividing the account into indexed and non-indexed propositions, we identify the individual trajectories and, after grouping them into categories, we elaborate the theoretical model. The project was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraiba, according to CAAE 20446513.0.000.5188. Results: The categories indicate that the conditions in which this group is affected by TB is not conducive to adhere to the treatment of the disease and will continue to do so, because they prioritize the needs of power, freedom, use of alcohol and other drugs. And despite suffering from the symptoms of the disease, they do not recognize it as an aggravation that requires immediate treatment and risk of death. Final considerations: We suggest that there be an articulation of health areas with social, nutritional and psychosocial assistance to find ways to intervene, in a favorable way, in the main barriers pointed out by RSPs affected by TB, so that they may adhere to treatment and give continuity to it. For this, it is necessary to look at the singularities of this group.